2016
DOI: 10.15406/jdvar.2016.03.00074
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Testing of Salmonella Spp. Bacteria Isolated from Samples Derived from Poultry on Antimicrobial Drugs

Abstract: Salmonellosis of poultry is a particularly significant problem in public health. The mere presence of Salmonella in poultry flocks and the emergence of salmonellosis caused great economic losses J Dairy Vet Anim Res. 2016;3(2):67-71. 67 AbstractIn accordance with the Ordinance on establishing measures for the early detection, diagnosis, prevention of spreading, suppression and eradication of poultry infection by certain Salmonella serotypes, antimicrobial agents are also applied in controlling salmonellas is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Similar findings (46.87%) were reported by earlier researchers in India [ 43 ]. But higher resistance against colistin (92.68%) was recorded in Bangladesh [ 47 ] and lesser (20%) in Serbia [ 48 ] and (4.76%) in Mumbai, India [ 49 ]. It is beyond the scope of this study to attribute colistin resistance to a particular reason.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings (46.87%) were reported by earlier researchers in India [ 43 ]. But higher resistance against colistin (92.68%) was recorded in Bangladesh [ 47 ] and lesser (20%) in Serbia [ 48 ] and (4.76%) in Mumbai, India [ 49 ]. It is beyond the scope of this study to attribute colistin resistance to a particular reason.…”
Section: Discussionmentioning
confidence: 99%
“…This class of antibiotics offers the advantage of oral administration, high potency against Gram negative organisms and low toxicity (Lee et al, 2004). However, Manic et al (2016) observed that enrofloxacin is not an effective drug in the treatment of salmonellosis of birds since Salmonella colonize the intestine after stoppage of the drug. It was also reported that the use of enrofloxacin can induce resistance in Campylobacter species (Velhner et al, 2013).…”
Section: Discussionmentioning
confidence: 99%